Patterns of peripheral vascular diseases at Muhimbili National hospital (Tanzania Medical Journal, 2009)
Background: Vascular diseases are emerging as a major health burden worldwide and vascular surgery is the major treatment of choice for these diseases. The treatment results in cosmetic and functional improvement. Purpose of the report is to show the commonly seen peripheral vascular disorders and treatment options offered at Muhimbili National hospital.Methods: Between September 2003 and October 2007 a total of 154patients with different vascular diseases (excluding intra- cranialconditions) were attended at Muhimbili National hospital. The ageof the patient ranged from 11 to ?55 years. The Sex, possible causes,surgical treatments offered and outcome were evaluated.Results: A total of 154 patients were studied. The average age of thepatients was 35 years, 58 being females and 96 being males. ThePatients were either self-referred or referred from district orregional hospitals. Majority had varicose veins, athero- or arteriosclerosis,deep venous thrombosis, abdominal aortic aneurysm, posttraumaticarterial pseudo-aneurysms and congenital arterial-venousmalformations. Few cases of thrombo-angiitis obliterans (Buerger’sdiseases) and HIV- vasculitis. A total of 97 patients (63%) weresurgically treated.Conclusion: Shortage of vascular surgeons and facilities in ourCountry needs to be sorted out to save life to these patients withvascular disorders.Key Words: Peripheral Vascular Diseases, and Shortage of Vascular Services in Tanzania.